2017
DOI: 10.1016/j.freeradbiomed.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of NOX2 activity in phagocytes mediated by ATM-kinase dependent phosphorylation

Abstract: NADPH oxidases (NOX) have many biological roles, but their regulation to control production of potentially toxic ROS molecules remains unclear. A previously identified insertion sequence of 21 residues (called NIS) influences NOX activity, and its predicted flexibility makes it a good candidate for providing a dynamic switch controlling the NOX active site. We constructed NOX2 chimeras in which NIS had been deleted or exchanged with those from other NOXs (NIS1, 3 and 4). All contained functional heme and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 57 publications
(63 reference statements)
0
17
0
Order By: Relevance
“…Phosphorylation of the C terminus is critical for the regulation of human NOXs. Phosphorylation of the NOX2 C terminus by protein kinase C enhances assembly of the multimeric NOX2 complex and its activity, whereas phosphorylation by ATM kinase inhibits NOX2 activity (Raad et al, 2009;Beaumel et al, 2017). NOX5 activity is regulated by Ca 21 binding to EF hands in the N terminus (Bánfi et al, 2004), but NOX5 is also activated by phosphorylation of the C terminus by protein kinase C a or calcium/calmodulin-dependent kinase II (Pandey et al, 2011;Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of the C terminus is critical for the regulation of human NOXs. Phosphorylation of the NOX2 C terminus by protein kinase C enhances assembly of the multimeric NOX2 complex and its activity, whereas phosphorylation by ATM kinase inhibits NOX2 activity (Raad et al, 2009;Beaumel et al, 2017). NOX5 activity is regulated by Ca 21 binding to EF hands in the N terminus (Bánfi et al, 2004), but NOX5 is also activated by phosphorylation of the C terminus by protein kinase C a or calcium/calmodulin-dependent kinase II (Pandey et al, 2011;Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PKC phosphorylation increased the electron transfer activity of the gp91 phox flavoprotein and the binding of its cytosolic domain to the cytosolic proteins Rac2, p67 phox and p47 phox . Recently , Beaumel et al have shown that gp91 phox is also phosphorylated on Ser486 located in the insertion sequence called NIS in PMA‐stimulated neutrophil‐like PLB‐985 cells . Ser486 is located within a consensus sequence targeted by the ataxia telangiectasia ‐mutated kinase (ATM kinase).…”
Section: Phosphorylation Of Gp91phox/nox2 and Nadph Oxidase Activatiomentioning
confidence: 99%
“…22 Recently, Beaumel et al have shown that gp91 phox is also phosphorylated on Ser486 located in the insertion sequence called NIS in PMA-stimulated neutrophil-like PLB-985 cells. 23 Ser486 is located within a consensus sequence targeted by the ataxia telangiectasia-mutated kinase (ATM kinase). Interestingly, inhibiting the ATM kinase enhanced NADPH oxidase activity, as did mutating Ser486 to Ala486, whereas the Ser486Glu mutation inhibited it.…”
Section: Phosphorylation Of Gp91 P H O X /Nox2 and Nadph Oxidase Acmentioning
confidence: 99%
“…Phosphorylation by protein kinase C (PKC) isoform at undetermined sites in the Cterminal domain was reported to increase electron flow activity and binding to p47phox, p67phox, and Rac2 in human neutrophils (291). More recently, Ser486 in the so-called NOX-specific insertion sequence in the C-terminal NADPHbinding region was suggested to be an inhibitory phosphorylation site targeted by ataxia telangiectasia mutated kinase (ATM) (26). Since the NOX2 complex activates ATM (26,387), this might constitute a negative feedback loop to terminate the NOX2 activity.…”
Section: Figmentioning
confidence: 99%
“…More recently, Ser486 in the so-called NOX-specific insertion sequence in the C-terminal NADPHbinding region was suggested to be an inhibitory phosphorylation site targeted by ataxia telangiectasia mutated kinase (ATM) (26). Since the NOX2 complex activates ATM (26,387), this might constitute a negative feedback loop to terminate the NOX2 activity. Interestingly, both ATM and PKC are expressed in skeletal muscle.…”
Section: Figmentioning
confidence: 99%